Effect of area ratio on base pressure in a suddenly expanded duct for under expanded flow ft mach 1.87 - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Khan, Mohammad Yunus (2012)
The results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage is presented in this paper. An active control in the form of micro jets is employed to control the base pressure. Air injection at four locations at the base, symmetric to the nozzle axis is used as the active control. The jet Mach number studied and the area ratios are 1.87, and 2.56, 3.24, 4.84, and 6.25. The L/D ratio is varied from 10 to 1. The experiments are conducted at a fixed level of under expansion (i.e. Pe/Pa = 1.5). In addition to base pressure, wall pressure field along the duct was also measured. As high as 80 percent increase in base pressure was achieved for certain combination of parameters of the present study. The minimum Length-to diameter ratio of the duct required is L/D = 2 for area ratios 6.25 and 4.84. Whereas, this requirement is L/D = 1 for area ratios 2.56 and 3.24.